2011
DOI: 10.1530/erc-11-0233
|View full text |Cite
|
Sign up to set email alerts
|

A novel human Smad4 mutation is involved in papillary thyroid carcinoma progression

Abstract: Smad proteins are the key effectors of the transforming growth factor b (TGFb) signaling pathway in mammalian cells. Smad4 plays an important role in human physiology, and its mutations were found with high frequency in wide range of human cancer. In this study, we have functionally characterized Smad4 C324Y mutation, isolated from a nodal metastasis of papillary thyroid carcinoma. We demonstrated that the stable expression of Smad4 C324Y in FRTL-5 cells caused a significant activation of TGFb signaling, respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Human Smad4 cDNA (1659 bp) was provided by Dr. Anna Coppa43 and subcloned into pcDNA3.1 (Invitrogen, Carlsbad, CA) with primer indicated in Supplementary Table S3. The 6Myc-tagged truncates and FLAG-tagged construct of Smad4 were provided by Dr. Ralf Janknecht44 and Dr. Caroline S. Hill45, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Human Smad4 cDNA (1659 bp) was provided by Dr. Anna Coppa43 and subcloned into pcDNA3.1 (Invitrogen, Carlsbad, CA) with primer indicated in Supplementary Table S3. The 6Myc-tagged truncates and FLAG-tagged construct of Smad4 were provided by Dr. Ralf Janknecht44 and Dr. Caroline S. Hill45, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…These cells were grown as previously described (8) in W/O supplemented with 5% calf serum and six-hormone mixture (6H) containing: TSH (10 mU/ml), insulin (10 μ g/ml), hydrocortisone (10 −8 M), transferrin (5 μ g/ml), glycyl-L-histidyl-L-lysyne acetate (10 ng/ml), and somatostatin (10 μ g/ml). Clones obtained by stable transfection of the FRTL-5 cells with the expression vector pEGFPC3 containing the human Smad4 cDNA wt or mutated, tagged with GFP, or with pEGFPC3 empty vector, were grown in F-12 Coon’s modification medium supplemented with 5% bovine serum and 6H mixture in presence of 500 μ g/ml of G418, as previously described (22). MDA MB468 (26), breast cancer cell lines purchased from American Type Culture Collection (ATCC, Rockville, MD), were grown in DMEM supplemented with 10% BS.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, TGF-β can exhibit tumor-promoting effects as observed in prostate and skin cancer progression (19,20) and in papillary thyroid carcinomas (21). We recently demonstrated that a Smad4 mutation, Smad4 C324Y, isolated from nodal metastases of papillary thyroid carcinoma, causes an increase of TGF-β signaling responsible for the acquisition of transformed phenotype and invasive behaviour in thyroid cells stable expressing this mutation (22). The TGF-β inhibitory growth response is also reduced in these cells, this finding is consistent with the observation that when Smad4 C324Y mutation is expressed in thyroid cells it exerts a clear pro-oncogenic function.…”
Section: Introductionmentioning
confidence: 99%
“…In PTC cell lines and animal models, TGF-β signaling has been shown to regulate cellular epithelial to mesenchymal transition [[10],[12],[13]]. Embryologically, TGF-β acts as a potent inducer of apoptosis, fundamental to normal development [[9]]. In adult cells, TGF-β retains its effect as a potent inducer of apoptosis, and also acts to promote immune regulation and angiogenesis, acting as a tumor suppressor gene [[8],[9],[11],[12]].…”
Section: Introductionmentioning
confidence: 99%
“…Embryologically, TGF-β acts as a potent inducer of apoptosis, fundamental to normal development [[9]]. In adult cells, TGF-β retains its effect as a potent inducer of apoptosis, and also acts to promote immune regulation and angiogenesis, acting as a tumor suppressor gene [[8],[9],[11],[12]].…”
Section: Introductionmentioning
confidence: 99%